Оцінка стоматологічного статусу дітей-інвалідів із психічними розладами - Гавриленко, Марина Аркадіївна; Gavrylenko, M. A. (My University, 2014)
Було обстежено 98 дітей-інвалідів із психічними розладами у віці від 2 до 18 років, які проживають у м. Запоріжжі та Запорізькій області. Виявлено низький рівень гігієни порожнини рота, високу поширеність захворювань твердих тканин зубів та зубощелепних аномалій. Approximately 14,4% of children disabilities are mental and behavior disorders. There are a number of problems in fulfilling the requirements of dental treatment protocols, when such a care is provided to children with mental disorders. This is connected with their special behavior: hyperkineses (motor disturbances), chronic tics, epileptic seizures, neurological reactions, hysteria, somatovegetative disorders (enuresis, vomiting), affect-respiratory attacks at the height of which respiratory arrests develop, a tendency to self-harm (pulling hair out, head beating, biting). Therefore, the study of dental status in children with mental disorders is a topical issue for the development of methods of treatment and preventive measures.
Evaluation of dental status in disabled children with mental disorders
Keywords: діти-інваліди з психічними розладами; зубощелепні аномалії; ускладнений карієс; низький рівень гігієни порожнини рота; disabled children with mental disorders; dentoalveolar anomalies; complicated caries; low level of oral hygiene